Sight in a Clique, Scent in Society: Plasticity in the Use of Nestmate Recognition Cues Along Colony Development in the Social Wasp Polistes dominula - Cini, Alessandro; Cappa, Federico; Pepiciello, Irene; Platania, Leonardo; Dapporto, Leonardo; Cervo, Rita (Frontiers in Ecology and Evolution, 2019)
Nestmate recognition, i.e. the ability to discriminate nestmates from foreign individuals, is a crucial feature of insect societies and it has been traditionally considered to be predominantly based on chemical cues. Recent empirical evidence however suggests a relevant plasticity in the use of different communication channels according to cue availability and reliability in different contexts. In particular, visual cues have been shown to influence various types of social recognition in several social insects, but their role in nestmate recognition is still under-investigated. We tested the hypothesis of plasticity in the use of visual and chemical recognition cues in the primitively eusocial wasp Polistes dominula, in which the availability and reliability of recognition cues varies across the colony cycle. Indeed, before the emergence of workers, P. dominula colonies are rather small (one to few individuals), and the variability in the facial pattern might allow resident wasps to use visual cues for nestmate recognition. After workers’ emergence, the increase in the number of colony members reduces the reliability of visual cues, thus leaving chemical cues as the most reliable nestmate recognition cues. We thus predict a differential use of chemical and visual cues along colony life. We experimentally separated visual and chemical cues of nestmates and non-nestmates and presented them alone or in combination (with coherent or mismatched cues) to resident wasps to test which communication channel was used in the two stages and, in case, how visual and chemical cues interacted. Our results show, for the first time in a social insect, the differential use of visual and chemical cues for nestmate recognition in two different phases of colony, which supports the hypothesis of a plastic, reliability-based use of recognition cues in this species according to the different colonial contexts.